'We can sh*t for another 10 years.' Toilet paper, pandemic politics and cultural citizenship. Issue 2 (4th March 2022) - Hermes, Joke; Kopitz, Linda
ABSTRACT: The global reality of the COVID-19/Corona pandemic paradoxically boosted national politics, broadcasting and citizenship. Media coverage, especially initially, praised citizen solidarity and the creative solutions that were pioneered to care for each other. A year later, a lasting social learning curve throughout and after this crisis seems illusory. The pandemic, this paper argues, needs to be understood in a longer timeframe as the working through and coming to terms with neo-liberal governmentality. The (often hilarious) early responses on social media provide a strong entry to do so. Our focus will be on the Netherlands which had a so-called 'intelligent' lockdown during the first wave of COVID-19 in the spring of 2020. Using the authors' own sharing back and forth of toilet paper memes as a starting point, we aim to explore the notion of collective self-reflection and citizen co-education underlying both heated and simply ridiculous posts. Using previous discussion of cultural citizenship, this paper inquires into how pandemic citizenship played out as a vast exercise in disciplining and distinction through jokes and anger. The material suggests a nostalgic turn that might point to an implicitly voiced critique of neoliberal governmentality.